Adoption of Robotic Process Automation in External Auditing Process in Metropolitan Indonesia: A Qualitative Approach - Evelin Candratio; Mayang Puti Harita; Ary Daniel Hartanto; Marko Sebira Hermawan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Currently, digital transformation is unavoidable. Digital transformation has an impact on increasing company performance and efficiency by making changes to the business process. In the audit process, Robotic Process Automation is one of the processes that could be done by the auditor in the audit implementation so it can be faster, more efficient and accurate, especially in data collection and initial analysis. RPA can assist auditors in collecting the necessary data in the audit process in a shorter time. The external auditor has a contract for a short period with the client, which is not necessarily extended to the next period, while the cost of implementing the RPA is quite high. The effort used in building, developing, and implementing RPA in an activity is very high. Meanwhile, the audit processes that can be assisted by RPA are still limited, as well as lack of effectiveness and efficiency. Lack of human judgment is one of the biggest challenges in implementing RPA.